THE ROLE OF INTERNATIONAL COMMERCIAL ARBITRATION IN THE DEVELOPMENT OF PUBLIC AND PRIVATE INTERNATIONAL LAW (Eureka Journal of Humanities and Social Research, 2026)
Over the past half century, International Commercial Arbitration (hereinafter “ICA”) has ceased to be merely a mechanism for resolving private law disputes; it has evolved into a constitutive actor in the evolution of both private international law (“PrIL”) and public international law (“PIL”). Sabahi, Laird and Gismondi express this situation strikingly and emphasize that the field of modern international investment law "public international law has a unique overlap with topics found in private international law" 2 .